Inflammatory Myofibroblastic Tumor of the Urinary Bladder: An 11-Year Retrospective Study From a Single Center - Chen, Can; Huang, Mengjun; He, Haiqing; Wu, Shuiqing; Liu, Mingke; He, Jun; Zang, Hongjing; Xu, Ran (Frontiers in Medicine, 2022)
Purpose: To provide our experience upon diagnosis and treatment of inflammatory myofibroblastic tumour of urinary bladder (IMTUB). Materials and Methods: A database search in the pathology archives of using the term “inflammatory myofibroblastic tumor” and” bladder” in our hospital department of pathology from 2010 to 2021. Patient characteristics, clinical features, histopathological results, immunohistochemical staining results and treatment outcomes were reviewed. Rusults: Fourteen cases of IMTUB were retrieved. The mean age was 44.7± 18.9 years. (range12–74). nine patients (64.3%) presented with haematuria, followed by seven (50.0%) with odynuria, five (35.7%) with urgent urination, one (7.1%) with dysuria. Ten patients (71.4%)were treated with partial cystectomy (PC), three (21.4%) with transurethral resection of bladder tumor (TURBT), and one (7.1%) with radical cystectomy (RC). Histopathologically,8 (57.1%) had a compact spindle cell pattern. Anaplastic lymphoma kinase (ALK) staining was positive in 6/8 (75.0%) of cases. During a mean follow-up period of 43.9 ±38.0 months (range 3–117). A patient occurred recurrence within half a month. Then treated with further TURBT surgery with no recurrence within 6 months. Thirteen patients had no any local recurrence or distant metastasis. Conclusion: IMTUB which runs a benign disease course is rare in clinic with good prognosis. The disease is mainly treated with surgery to remove the tumor completely. It can easily be misdiagnosed as bladder urothelial carcinoma, leiomyosarcoma and rhabdomyosarcoma, which may result in overtreatment and poor quality of life for patients.